2022
DOI: 10.1186/s13104-022-06180-3
|View full text |Cite
|
Sign up to set email alerts
|

SARS CoV- 2 vaccination induces antibodies against cardiolipin

Abstract: Objective Cases of thrombosis have been reported after administration of SARS-CoV-2 vaccines, with controversial results relating to Oxford-AstraZeneca’s ChAdOx1-S. Despite such cases being rare, they still raised concerns for their involvement in coagulopathies. Anti-cardiolipin (aCL) IgG antibodies have been linked to venous and arterial thrombosis. The aim was to evaluate the concentration of aCL IgG antibodies in vaccinated and COVID-19 positive individuals using indirect ELISA and commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
(3 reference statements)
0
10
0
Order By: Relevance
“…It remains to be seen whether weak aCL antibody positivity could also be related to COVID-19 vaccination or part of the epitope spreading cascade in our patient. Recent research around this phenomenon is conflicting, with some studies reporting a link between COVID-19 vaccination and development of antiphospholipid antibodies, 27 and others reporting no link between vaccination and antiphospholipid antibody production. 28 The patient in case 2 did not have any clinical consequences associated with positive aCL titers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains to be seen whether weak aCL antibody positivity could also be related to COVID-19 vaccination or part of the epitope spreading cascade in our patient. Recent research around this phenomenon is conflicting, with some studies reporting a link between COVID-19 vaccination and development of antiphospholipid antibodies, 27 and others reporting no link between vaccination and antiphospholipid antibody production. 28 The patient in case 2 did not have any clinical consequences associated with positive aCL titers.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the study that showed that although aCL levels are higher in Pfizer-vaccinated patients, these positive levels are not clinically pathogenic. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Another notable result reported here is that none of the antibodies against any SARS-CoV-2 protein cross-reacted with CL which, like PF4, is a target of autoantibodies in most COVID-19 coagulopathies. Anti-CL IgG and IgM are rarely (4.5–5.7 and 6.4–6.6%., respectively) observed in COVID-19 hospitalized patients who are not diagnosed with thrombosis [ 26 , 34 ] but anti-CL IgG and IgM antibodies are present in 52% and 40%, respectively, of COVID-19 patients admitted to intensive care and are highly associated with thrombotic events [ 96 ]. CL (3-bis(sn-3’-phosphatidyl)-sn-glycerol) is a phospholipid that is found as a normal component of blood plasma as well as the mitochondrial membrane.…”
Section: Discussionmentioning
confidence: 99%
“…It is not found in any known virus but is common to the cell membranes of all the bacterial species studied here [ 40 ]. Thus, a number of studies have recently reported that vaccination with the SARS-CoV-2 vaccines (adjuvanted and adenovirus vectored) fails to induce anti-CL antibodies [ 96 , 97 , 98 , 99 ]. These studies using human sera and polyclonal antibody preparations are consistent with our observation of the lack of cross-reactivity between SARS-CoV-2 or adenovirus rodent antibodies and CL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation